Leptomeningeal Spread in Glioblastoma: Diagnostic and Therapeutic Challenges. (31st August 2020) - Birzu, Cristina; Tran, Suzanne; Bielle, Franck; Touat, Mehdi; Mokhtari, Karima; Younan, Nadia; Psimaras, Dimitri; Hoang‐Xuan, Khe; Sanson, Marc; Delattre, Jean‐Yves; Idbaih, Ahmed
Abstract: Background: Glioblastoma (GBM) is the most common and aggressive primary malignant brain tumor. Leptomeningeal spread (LMS) is a severe complication of GBM, raising diagnostic and therapeutic challenges in clinical routine. Methods: We performed a review of the literature focused on LMS in GBM. MEDLINE and EMBASE databases were queried from 1989 to 2019 for articles describing diagnosis and therapeutic options in GBM LMS, as well as risk factors and pathogenic mechanisms. Results: We retrieved 155 articles, including retrospective series, case reports, and early phase clinical trials, as well as preclinical studies. These articles confirmed that LMS in GBM remains (a) a diagnostic challenge with cytological proof of LMS obtained in only 35% of cases and (b) a therapeutic challenge with a median overall survival below 2 months with best supportive care alone. For patients faced with suggestive clinical symptoms, whole neuroaxis magnetic resonance imaging and cerebrospinal fluid analysis are both recommended. Liquid biopsies are under investigation and may help prompt a reliable diagnosis. Based on the literature, a multimodal and personalized therapeutic approach of LMS, including surgery, radiotherapy, systemic cytotoxic chemotherapy, and intrathecal chemotherapies, may provide benefits to selected patients. Interestingly, molecular targeted therapies appear promising in case of actionable molecular target and should be considered. Conclusion: As the prognosis of glioblastoma is improving over time, LMS becomes a more common complication. Our review highlights the need for translational studies and clinical trials dedicated to this challenging condition in order to improve diagnostic and therapeutic strategies. Implications for Practice: This review summarizes the diagnostic tools and applied treatments for leptomeningeal spread, a complication of glioblastoma, as well as their outcomes. The importance of exhaustive molecular testing for molecular targeted therapies is discussed. New diagnostic and therapeutic strategies are outlined, and the need for translational studies and clinical trials dedicated to this challenging condition is highlighted. Abstract : This article reviews diagnostic tools and applied treatments for leptomeningeal spread, a severe complication of glioblastoma raising diagnostic and therapeutic challenges in clinical routine. The importance of molecular testing and its importance in the setting of molecular targeted therapies is also reviewed.